Role of giant corporations (Washington, D.C. : United States Government, 1973)
This book is on the role of Giant Corporations.
Hearings before the Subcommittee on Monopoly of the Select Committee on Small Business. United States Senate Ninety-second Congress first session on the role of giant corporations in the American and world economies.
Includes appendices in part 2B.
gp 22/01/2019
Ref
Keywords: Antitrust law; Automobile industry and trade; Big business; United States